Periodic EEG complexes in infectious mononucleosis encephalitis. Issue 7 (July 1982) - Greenberg, D A; Weinkle, D J; Aminoff, M J
Abstract : The presence of periodic EEG complexes in patients with an acute viral encephalitis is generally held to suggest that infection is due to herpes simplex. We now report a patient with clinical and laboratory findings of infectious mononucleosis, and neurologic involvement manifested by lymphocyte meningitis, coma, seizures, aphasia, hemiparesis and hemianopsia. Serial EEGs showed periodic, predominantly left-sided slow wave complexes occurring every 4 to 5 seconds, which disappeared with clinical resolution of the illness. In view of our findings and the similar findings reported previously by others in another case of infectious mononucleosis encephalitis, an EEG showing periodic complexes in the clinical setting of acute viral encephalitis should not be considered pathognomonic of herpes encephalitis, and infectious mononucleosis should be included in the differential diagnosis.